2018
DOI: 10.1002/job.2330
|View full text |Cite
|
Sign up to set email alerts
|

On the origins of informal hierarchy: The interactive role of formal leadership and task complexity

Abstract: Summary Informal hierarchies are a common and important feature of many groups, yet we know little about the antecedent conditions that determine the strength of such hierarchies. Building on theory that has depicted hierarchy as a mechanism for reducing uncertainty and creating structure, we posit that informal hierarchies emerge most strongly in situations that are ambiguous, ill‐defined, and unstructured. Three independent studies confirm this notion, demonstrating that groups develop particularly strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 90 publications
2
23
1
Order By: Relevance
“…Similar to previous research, informal hierarchy strength is maximized when every dyadic pairing has asymmetric deference (Bunderson et al, 2016;Oedzes et al, 2019). Accordingly, we adopted a dyadic approach to measure deference asymmetries that was then aggregated into a network measure of informal hierarchy strength.…”
Section: Informal Hierarchy Strengthmentioning
confidence: 95%
See 3 more Smart Citations
“…Similar to previous research, informal hierarchy strength is maximized when every dyadic pairing has asymmetric deference (Bunderson et al, 2016;Oedzes et al, 2019). Accordingly, we adopted a dyadic approach to measure deference asymmetries that was then aggregated into a network measure of informal hierarchy strength.…”
Section: Informal Hierarchy Strengthmentioning
confidence: 95%
“…Because project teams undergo predictable shifts in pressure (Gersick, 1989(Gersick, , 1994, they are well-suited for predicting when and how informal hierarchy strength will change over time. Additionally, selfmanaged project teams do not have a formal leader who could create endogeneity issues by affecting informal hierarchy strength through actions such as changing members (e.g., Oedzes et al, 2019).…”
Section: Informal Hierarchy Strength Changes and Their Effect On Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Hierarchy of company has also great impact on the company prosperity; informal hierarchies are a common and important feature of many groups, yet we know little about the antecedent conditions that determine the strength of such hierarchy. [17] Modern sexist beliefs are currently emerging as one of the most important barriers to achieving gender equality in managerial positions in organizations. [18] The other study found that the main SHS Web of Conferences 9 2, 0 (2021) Globalization and its Socio-Economic Consequences 2020 barriers in women's career enhancement were work-life imbalance, subordinates' perceptions regarding women leaders, social networking, and personal factors.…”
Section: Management From the Aspect Of Diversity In Era Of Globalizationmentioning
confidence: 99%